Is labor force participation detrimental to the mental health of rural older adults? The mediating role of attitudes toward aging - Liu, Yanjun; Ji, Xiaoyuan (Frontiers in Public Health, 2025)
BackgroundPopulation aging is a significant global issue. In China, the widening urban-rural disparity in population aging has contributed to problems such as the hollowing out of rural areas and a decline in the labor force. This situation, in turn, has subjected older adults in rural areas to significant psychological pressure. Thus their mental health has been widely emphasized. This study is dedicated to analyzing the linkages between mental health, attitudes toward aging, and their labor force participation among rural Chinese older adults in order to promote the construction of an age-friendly social system.MethodsBased on data from the 2020 China Longitudinal Aging Study (CLASS), this study selected rural household residents aged 60 and above as its research subjects. Correlation analysis examined the relationships among labor force participation, mental health among older adults, and attitudes toward aging. OLS regression model was used to investigate the impact of labor force participation on mental health. Stepwise regression and Bootstrap mediation analysis were applied to test the mediating role of attitudes toward aging. Propensity Score Matching was utilized to address endogeneity issues, ensuring the robustness of the findings.Results(1) This study finds that labor participation significantly promotes the mental health of rural older adults, manifested explicitly in reduced depressive symptoms. However, this beneficial effect exhibits a threshold, resulting in a “U-shaped” impact where the influence of labor participation first increases and then decreases. (2) Mechanism analysis further reveals that labor participation enhances older people’s mental health by shaping positive attitudes toward aging. (3) Notably, the mediating mechanism of positive aging attitudes transforms labor participation from a potential health risk in old age into a key protective factor for mental well-being.ConclusionResearch findings confirm that Depression Scales serve as crucial indicators for assessing mental health among older adults. Labor participation is a significant psychological protective factor for rural seniors in China. Moderate labor effectively alleviates depressive symptoms and enhances overall mental well-being in this demographic, whereas excessive or relentless labor yields adverse effects. Mechanism analysis indicates that labor participation helps older adults develop positive attitudes toward aging, thereby buffering and mediating the process by which potential health risks are transformed into psychological protective factors. This empirical study provides crucial evidence for policymakers to optimize rural labor force policies and establish intervention systems for active aging.